Bandung Institute of Technology Students’ Perspective on The Formation of Military Reserve through a State Defence Program - Ichwandini, Zahra Nur; Meilyna, Sherleen; Henly, Calista Marchia; Gunawan, Catherine Marta; Rahutami, Gayuh Tri; Fachrezzi, Rezda Abdullah; Rafifah, Muthia (Jurnal Pendidikan Ilmu Sosial, 2021)
State Defence Program is a program held by the Indonesian government in the efforts to form backup military troops which consist of citizens, combining military roles with a civil career which is called Military Reserve (Komponen Cadangan). This program is aimed at the general public as a place to develop human resources, especially the younger generation who are the nation’s successors. There has been a discourse around implementing military education through State Defence’s education program as one of the backups for defense and security in Indonesia, which raises pros and cons among citizens. This program’s main targets are the nation’s youth, which includes university students. Efforts are made with plans for collaboration between State Defence and Independent Campus (Kampus Merdeka) programs. Hence, an analysis of university students’ opinion about this program has to be done to give us an illustration that is useful for the government and citizens. Writers’ method in analysing is done by collecting data from a survey, in which the respondent target is university students to see their perspectives about the program.